HOUT-29. HEALTHCARE COSTS FOR HIGH-GRADE GLIOMAS: A POPULATION-BASED STUDY. (5th November 2018) - Liu, Yang; Tyler, Evan; Lustick, Martin; Klein, David; Walter, Kevin
Abstract: Clinical management of patients with high-grade gliomas (HGGs) is very challenging both clinically and financially. As costs of cancer care in the US are expected to increase and oncology care is switching from volume-based to value-based pattern, efforts are needed to establish effective and efficient management of patients with HGGs. However, relevant data are limited. In this study, we retrospectively identified 88 primary HGGs patients diagnosed and treated at our institution between January 1, 2011 and February 28, 2017 and linked patient clinical information from electronic health record with all insurance claims data (all paid) from Excellus BCBS. Among these patients, the median age at diagnosis was 59 years and the majority of the patients were white (94.3%) with GBM (80.7%). Total median healthcare costs for clinical management of HGGs were 184, 159.83 (95% CI: 151, 214.98, 222.431.36). The largest component of healthcare costs was outpatient service, followed by inpatient costs. When we examined costs by service type, we found the leading cost was radiology service, followed by inpatient surgical, prescription drugs, inpatient medical and outpatient pharmacy. Compared with patients under non-commercial insurance, patients under commercial insurance had longer survival time (median: 411 days vs. 358 days, p = 0.563), higher healthcare costs in total (235, 732.85 vs. 142, 134.07, p < 0.001), and in each phase of clinical care. We further observed a U-shaped curve healthcare costs pattern, i.e., healthcare costs were high in the phase of initial care (3-month after diagnosis) and 9-month after initial diagnosis with relative low between these two phases. Generalized linear model showed patients with commercial insurance, better Karnofsky Performance Status, longer survival time had higher healthcare costs. Our real-world study demonstrated that healthcare costs for patients with HGGs were substantial and such high healthcare costs were positively associated with patient survival and commercial insurance.